Pengaruh Manajemen Mutu Sumber Daya Manusia Dan Budaya Organisasi Terhadap Kinerja Guru Di MTs Negeri 6 Jombang - Lailatusholihah, Lailatusholihah; Suwandi, Suwandi (CV. Ulil Albab Corp, 2024)
Teacher performance can be interpreted as the level of success of teachers in carrying out tasks in accordance with their responsibilities and authority based on performance standards that have been set during a certain period within the framework of achieving educational goals. This research has the objectives, (1) To find out whether there is an influence of human resource quality management on teacher performance at MTs Negeri 6 Jombang, (2) To find out whether there is an influence of organizational culture on teacher performance at MTs Negeri 6 Jombang dan (3) To find out whether there is a simultaneous influence of human resource quality management and organizational culture on teacher performance at MTs Negeri 6 Jombang. The results of this research show that, (1) Human Resource Quality Management has a significant effect on teacher performance. This can be proven based on the results of the hypothesis test (in the form of a T test significance value with a significance value of 0.000 < 0.05 and a T count result of 14,238 (14,238 > 2.019), so Ho is rejected and Ha is accepted. (2) It also states that organizational culture has a significant effect on performance. teacher. This can be proven based on the results of the hypothesis test (in the form of a significance value of 0.000 < 0.05 and a T count of 15.176 (15.176> 2.019) so Ho is rejected and Ha is accepted dan (3) Human Resource Quality Management and Organizational Culture have a significant simultaneous effect on Teacher Performance at MTs Negeri 6 Jombang. This can be proven based on the calculated F value (in the form of a significance value of 0.000 < 0.005 and the calculated F result is 120.044 (120.044 > 2.84) so Ho is rejected and Ha is accepted